Cover Image, Volume 119, Number 3, March 2018. Issue 3 (27th January 2018) - Olotu, Fisayo A.; Soliman, Mahmoud E.S.
Abstract : Cover : The cover image, by Fisayo A. Olotu and Mahmoud E.S. Soliman, is based on the Research Article From mutational inactivation to aberrant gain‐of‐function: Unraveling the structural basis of mutant p53 oncogenic transition, DOI: 10.1002/jcb.26430 .